Can we predict dividend cuts? - Onali, Enrico (Elsevier, 2016)
I examine the predictability of dividend cuts based on the time interval between dividend announcement dates using a large dataset of US firms from 1971 to 2014. The longer the time interval between dividend announcements, the larger the probability of a cut in the dividend per share, consistent with the view that firms delay the release of bad news.